Drogues des villes et drogues des champs. Les pratiques d’usage et de revente féminines en France - Perrin, Sarah (Déviance et société, 2022)
Based on a corpus of 42 interviews with women who use and/or sell drugs, both in a rural population and an urban one, this article focuses on the influence of living spaces on female drug-related practices. By retracing the trajectories of these two groups, the focus is to highlight a population too often studied through the prism of urbanity, masculinity, and precarity. By shifting the focus and through comparison, this article attempts to show differentiated practices of drug use and drug sales, repressive risks and gendered strategies in rural and urban areas, according to lifestyles and geographical location.